Cloned embryonic DNA sequences flanking the mouse immunoglobulin C gamma 3 and C gamma 1 genes. - Adams, J M (1980)
To investigate the DNA surrounding genes for immunoglobulin heavy chain constant (CH) regions, we have isolated two clones bearing a C gamma 3 gene and two bearing a C gamma 1 gene from a library of mouse embryo DNA fragments. The C gamma 3 clones span 8.6 kilobase pairs (kb) on the 5' side of the gene and 6.7 kb on its 3' side, while the C gamma 1 clones together span 13 kb of 5' flanking sequence and 2.5 kb of 3' flanking sequence. Restriction mapping of the C gamma 3 gene indicates that intervening sequences divide the gene into segments of domain size, as in other CH genes. Hybridization of clone fragments to restriction digests of mouse DNA indicates that both the C gamma 1 and C gamma 3 genes probably occur as single copies in the genome. Moreover, the entire cloned sequences on the 5' side of both genes appear to be unique in the genome, indicating that no large common sequences flank CH genes. Restriction data suggest that the C gamma 3 gene is 37-40 kb 5' to the C gamma 1 gene.